A Novel Differentially Fed Compact Dual-Band Implantable Antenna for Biotelemetry Applications - Liu, Y.; Chen, Y.; Lin, H.; Juwono, Filbert Hilman (Institute of Electrical and Electronics Engineers, 2016)
© 2016 IEEE. A novel differentially fed dual-band planar antenna operating at the Medical Implant Communication Service band (402-405 MHz) and the Industrial, Scientific, and Medical band (2400-2480 MHz) is presented. The measured 10-dB differential reflection coefficient bandwidth is 389-419 MHz (7.4%) at the lower band and 2395-2563 MHz (6.6%) at the upper band, respectively. With the use of symmetric meandered strip and shorting pin, a differentially fed compact dual-band design is obtained, where the volume of the prototype is only 642.62 mm3 (22 mm × 23 mm × 1.27 mm). Due to its small size and dual-band operation, the proposed antenna can be connected to differential circuits in implantable biotelemetric devices.